Diabetes Self-Management and Its related Factors - Titis Kurniawan; Kurniawan Yudianto (Faculty of Nursing Universitas Padjadjaran, 2016)
Self-management is essential in preventing complications among patients with Diabetes Mellitus. The behaviourof patients to implement Diabetes Self-Management (DSM) is influenced by several factors which needsfurther study. This descriptive study aimed to identify factors contributing to DSM among patients with Type2 Diabetes Mellitus (DMT2). 94 respondents were recruited using randomized sampling obtained from aninpatient unit in one hospital in West Java province. Self-rating instruments were used to identify demographydata, knowledge about DSM, self-efficacy scale, and DSM questionnaire. Descriptive analysis was conductedto explain demography data, knowledge, self-efficacy and DSM. Findings indicated respondents demonstratedmoderate level of knowledge (M=7,53), and self-efficacy (M=34,8), and high level of DSM (M=89,28).Post-hoc analysis demonstrated a significant relationship between age (r=-0,209); p=0,043), education level(p=0,008), and self-efficacy (r=0,214; p= 0,038). No significant relationship was not identified with DSM(r=0,317; p=0,187). It is concluded that age, level of education, and self-efficacy were contributed to DSM.